Development of Spatio-Temporal Database Prototype For Management of 4-Dimensional Cadastre Object In Indonesia - Miranty Noor Sulistyawati; Trias Aditya; Purnama Budi Santosa (Universitas Gadjah Mada, 2019)
The dynamics of the Indonesian population has increased causing the need for cadastral objects to increase. 2D and 3D cadastral objects change over time. Cadastral objects have spatial and juridical data changes every day. These changes can be caused by the transfer of rights, changes of rights, split and merging cadastral objects. Changes are recorded and stored as a history of cadastral objects (4-dimensional cadastre). Historical data on cadastral objects can be categorized as one of the big data in the cadastre sector, based on the frequency of recording data. The data can be used to track changes in cadastral objects so that they can avoid disputes. Spatial data in this case is very vulnerable data to cause disputes if the shape, position and size do not match the conditions in the field, and need special attention in integrating with the juridical data. This paper aims to identify methods for storing spatial data of 4D cadastral objects that are suitable for Indonesia. The importance of storing cadastral objects and their history causes researchers and cadastre experts in the world to formulate international standards in managing spatial and juridical data along with a history of cadastral objects (4D cadastre). LADM is an international standard conceptual model (ISO 19152) which can show the legacy of a cadastral object expressed in RRR (Rights, Restriction and Responsibility). In LADM, there is a VersionedObject class that represents various versions or a history of spatial units, object registration, owner and administration. Several studies conducted by researchers in the world were compared in this paper to find methods for applying LADM and VersionedObject classes. That methods were implemented in this paper to design a database of spatio-temporal 4D cadastre. Finally a prototype of spatial-temporal database will be produced to manage 4D cadastral objects.